The Role and Regulatory Mechanism of Hippo Signaling Components in the Neuronal System - Cheng, Jinbo; Wang, Shukun; Dong, Yuan; Yuan, Zengqiang (Frontiers in Immunology, 2020)
The Hippo signaling pathway, an evolutionarily conserved protein kinase cascade, plays a critical role in controlling organ size, cancer development, and tissue regeneration. Recently, mounting evidence has suggested that Hippo signaling also has an important role in regulating immunity, including innate and adaptive immune activation. In the neuronal system, Our laboratory results, together with those from other studies, demonstrate that the Hippo signaling pathway is involved in neuroinflammation, neuronal cell differentiation, and neuronal death. In the present review, we summarize the recent findings pertaining to the function and regulatory mechanism of Hippo signaling components in the neuronal system, implicating the potential of Hippo signaling as a therapeutic target for the treatment of neuronal system diseases.